Construction of Reality and Segregative Content of Islamic Media - Taufik, Cevi Mochamad; Sila, Gita Eka (Communicatus: Jurnal Ilmu komunikasi, 2023)
Islamic media still faces obstacles in becoming the host for hundreds of millions of Indonesian Muslims. The barriers faced are fundamental because they relate to media management techniques and the values embodied in the news. In practice, noble Islamic values will have difficulties when constructed in various events presented as information content. This difficulty continues in the transformation of media platforms that transform into online forms. As a result, the power of the media is still controlled by the popular press with liberal tendencies. To look further at the obstacles faced, this study aims to find out, first, the form of construction of the reality of Islamic media and, secondly, the packaging of Islamic media content that is presented so that Islamic press is challenging to become the primary reference in fulfilling the information needs of the ummah. The method used in this study is descriptive qualitative with qualitative content analysis techniques by analyzing several Islamic media. As a result, the construction form of Islamic media prioritizes internalization rather than externalization and objectification in making news. In contrast, the content produced in presenting the report is segregative because it only displays content containing Islamic rules and laws so that the messages conveyed by Islamic media are still specific and given minimally. The essential information that the audience wants to know immediately.